Lysine Methylation Modulates the Interaction of Archaeal Chromatin Protein Cren7 With DNA - Ding, Niannian; Chen, Yuanyuan; Chu, Yindi; Zhong, Cheng; Huang, Li; Zhang, Zhenfeng (Frontiers in Microbiology, 2022)
Cren7 and Sis7d, two chromatin proteins from Sulfolobus islandicus, undergo extensive methylations at multiple lysine residues to various extents. Whether this highly conserved protein serves an epigenetic role in the regulation of the structure and function of the chromosome remains unclear. In the present study, we show that methylation significantly affects Cren7, but not Sis7d, in the ability to bind DNA and to constrain negative DNA supercoils. Strikingly, methylated Cren7 was significantly less efficient in forming oligomers or mediating intermolecular DNA bridging. Single-site substitution mutation with glutamine reveals that methylation of the four lysine residues (K24, K31, K42 and K48) of Cren7 at the protein-DNA interface, which are variably conserved among Cren7 homologues from different branches of the Crenarchaeota, influenced Cren7-DNA interactions in different manners. We suggest that dynamic methylation of Cren7 may represent a potential epigenetic mechanism involved in the chromosomal regulation in crenarchaea.